2022
DOI: 10.3389/fpls.2022.895720
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity Distribution and Climatic Niche of Samara Species in China

Abstract: Studying the distribution of samara species is of ecological and economic significance. This information helps us with understanding species dispersal mechanisms, evaluating the risk of invasive species, and the management of ecological forests. However, limited research has explored, on a large scale, the geographic distribution of samara species and their influential abiotic factors. Here, we use the distribution data of 835 vascular samara species and growth form data to explore their geographic patterns in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that height is a crucial trait in determining species fitness (Westoby et al, 2002;Dıáz et al, 2016;Thomson et al, 2018;Du et al, 2022). Fertilization and removal experiments conducted on the Qinghai-Tibet Plateau have also shown that height differences play a dominant role in species fitness differences, species coexistence, and productivity in alpine grassland plant communities (Liu et al, 2016).…”
Section: Species Removal Experimentsmentioning
confidence: 99%
“…Numerous studies have demonstrated that height is a crucial trait in determining species fitness (Westoby et al, 2002;Dıáz et al, 2016;Thomson et al, 2018;Du et al, 2022). Fertilization and removal experiments conducted on the Qinghai-Tibet Plateau have also shown that height differences play a dominant role in species fitness differences, species coexistence, and productivity in alpine grassland plant communities (Liu et al, 2016).…”
Section: Species Removal Experimentsmentioning
confidence: 99%